Urgency of Marine Resources Supervision Regulation by North Sulawesi Regional Government to Realize Sustainable and Fair Management - Rahmatia, Rahmatia; Juwita, Juwita (Jurnal Indonesia Sosial Sains, 2025)
This study examines the urgency and formulation of marine resource supervision regulations by the Regional Government of North Sulawesi Province in realizing sustainable and equitable management. The research method used is normative juridical with an analytical descriptive approach based on the study of laws and regulations, official documents, and related literature. The results of the study emphasized the need for regulations that integrate the principles of environmental sustainability, the principles of distributive and participatory justice, as well as adaptive and technology-based supervisory mechanisms. Ideal regulations must also provide clear and flexible authority to local governments by synchronizing policies with the central government level to avoid overlapping authority. Increasing institutional capacity and the active role of coastal communities are the key to effective supervision. This research provides recommendations for regulatory formulation that harmonizes legal, social, and ecological aspects in order to achieve fair and sustainable management of marine resources in North Sulawesi.